OIL-ENVIRONMENTAL DEGRADATION AND HUMAN SECURITY IN THE NIGER-DELTA REGION OF NIGERIA: CHALLENGES AND POSSIBILITIES - Akhakpe, Ighodalo (European Scientific Journal, ESJ, 2012)
The Niger-delta region has continued to attract scholarly attention in view of devastation of its environment and people due to failure to manage the negative consequences of oil exploitation and underdevelopment it has spawned in the region. The problem of oil environmental degradation and human insecurity it has elicits have not been lost to the federal government and its oil-petrol dollar partners. Yet, not much have been done to control the effect of oil exploitation in the region that has left the environment desecrated and the people in abject poverty. Also, development of the region has been almost non-existence in spite, of the enormous revenue accruing to the federal, state and local governments from the region. Recent oil spill and slow pace of development in the area have revived calls for human security in this part of Nigeria. The Paper submitted that although the present civilian administration has made major efforts to ameliorate the suffering of the people of the region, their conditions remain pitiable and unless the present government’s efforts are directed towards improving the peoples’ socio-economic and political conditions, the restiveness and violence in the Niger-Delta region in particular and Nigeria in general would continue unabated.